Penerapan Imajinasi Terbimbing Terhadap Tingkat Kecemasan pada Pasien Folikular Limfoma di RSUP X: Studi Kasus: Application of Guided Imagery to Anxiety Levels in Follicular Lymphoma Patients at RSUP X: A Case Study - Desty Greselly; Sriyati (Journal of Nursing Education and Practice, 2026)
Introduction: Follicular lymphoma is a subtype of non-Hodgkin lymphoma characterized by an indolent and chronic disease course that may lead to significant physical and psychological burdens, including anxiety, particularly in patients undergoing long-term treatment. Anxiety in cancer patients can negatively affect quality of life, highlighting the need for safe and effective non-pharmacological nursing interventions. Objective: This case report aimed to describe the application of guided imagery therapy as part of nursing care in a patient with follicular lymphoma experiencing anxiety. Methods: A descriptive case study was conducted on a single patient diagnosed with follicular lymphoma at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Nursing care was delivered through the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Guided imagery therapy was administered for 20 minutes per session over three consecutive days. Anxiety levels were measured using the Hospital Anxiety and Depression Scale-Anxiety (HADS-A) before and after the intervention. Results: A 74-year-old female patient presented with an initial HADS-A score of 12, indicating moderate to severe anxiety. After three sessions of guided imagery therapy, the HADS-A score decreased to 5, indicating a normal range. In addition to score reduction, the patient reported improved relaxation and reduced anxiety symptoms. However, these changes should be interpreted cautiously as a single-case outcome potentially influenced by other factors such as family support and adaptation to hospitalization. Conclusion: The application of guided imagery therapy in this case was associated with a reduction in anxiety levels in a patient with follicular lymphoma. This finding suggests that guided imagery may serve as a supportive nursing intervention for anxiety management in cancer patients. Nevertheless, the results are not generalizable, and further studies with larger samples and stronger designs are needed.